### Welcome to our community

#### Prove It

##### Well-known member
MHB Math Helper
Find the Inverse Laplace Transform of \displaystyle \begin{align*} F(s) = \frac{4s^3 + 5s^2 + 57s + 45}{\left( s^2 + 9 \right) ^2} \end{align*}
\displaystyle \begin{align*} \frac{A\,s + B}{ s^2 + 9} + \frac{C\,s + D}{ \left( s^2 + 9 \right) ^2 } &\equiv \frac{ 4s^3 + 5s^2 + 57s + 45}{ \left( s^2 + 9 \right) ^2 } \\ \left( A\,s + B \right) \left( s^2 + 9 \right) + C\,s + D &\equiv 4s^3 + 5s^2 + 57s + 45 \\ A\,s^3 + 9A\,s + B\,s^2 + 9B + C\,s + D &\equiv 4s^3 + 5s^2 + 57s + 45 \\ A\,s^3 + B\,s^2 + \left( 9A + C \right) \, s + 9B + D &\equiv 4s^3 + 5s^2 + 57s + 45 \end{align*}
Thus \displaystyle \begin{align*} A = 4, B = 5, C = 21, D = 0 \end{align*}, giving
\displaystyle \begin{align*} F(s) &= \frac{4s + 5}{ s^2 + 9 } + \frac{21s}{ \left( s^2 + 9 \right) ^2} \\ &= \frac{4s}{s^2 + 9 } + \frac{5}{s^2 + 9} + \frac{21s}{ \left( s^2 + 9 \right) ^2 } \\ &= 4 \left( \frac{s}{s^2 + 3^2 } \right) + \frac{5}{3} \left( \frac{3}{s^2 + 3^2} \right) + \frac{7}{2} \left[ -\frac{\mathrm{d}}{\mathrm{d}s} \left( \frac{3}{s^2 + 3^2} \right) \right] \end{align*}
\displaystyle \begin{align*} f(t) = 4\cos{ \left( 3t \right) } + \frac{5}{3} \sin{ \left( 3t \right) } + \frac{7}{2} t\sin{ \left( 3t \right) } \end{align*}